The role of zakat in economic recovery during and after the Covid-19 pandemic: A case study of Baznas in Indonesia - Prasetyoningrum, Ari Kristin (Journal of Islamic Economics Management and Business (JIEMB), 2023)
The Covid-19 pandemic has had a significant impact on the global economy, including Indonesia, which experienced a drastic economic decline. Baznas is expected to contribute to economic recovery through the management and distribution of zakat, infāq, and ṣadaqah (ZIS) funds. This study aims to evaluate the role of Baznas in supporting Indonesia’s economic recovery during and after the Covid-19 pandemic and to analyze the economic recovery methods implemented by Baznas. This research employs a qualitative approach with content analysis and literature review methods. Secondary data were obtained from Baznas activity reports, financial reports, and management reports from 2020 to 2022, sourced from the official Baznas website. The findings indicate that Baznas has effectively managed and distributed ZIS funds to assist communities affected by the pandemic. Various programs, including health, social, economic, and educational assistance, were implemented to mitigate the negative impacts of the pandemic. The distribution of ZIS funds was focused on both consumptive and productive schemes, with a greater emphasis on consumptive schemes during the pandemic. This study demonstrates that zakat, as an Islamic financial instrument, can be a solution to alleviate the economic burden on communities affected by Covid-19.